Effect of the thermal processing (Pasteurization and sterilization) on the quality of Calamay (Ground sticky rice dessert). - Bunao, Rica Salupan
Calamay, a sweet ground sticky rice dessert, is one of the most popular pasalubong items from the province of Bohol. However, it is highly perishable with less than a week of shelf-life. This study aimed to apply thermal pasteurization and sterilization to calamay packaged in glass jars to improve its shelf-life while monitoring its quality. For a 30-minute holding time at the product cold spot, reference temperatures of 90°C for pasteurization and 121.1°C for sterilization yielded F-values of 59.39 minutes and 64.68 minutes, respectively. These were above the required minimum F-value by FAO (2022) due to overprocessing from the temperature fluctuations caused by the difficult manual control of heat source during the process. It was found out that only the sterilized calamay samples were commercially sterile as its time-temperature combination was adequate to eliminate the target microorganism Clostridium botulinum. Nevertheless, it was proven that both thermal processes successfully extended the shelf-life of calamay as no molds were observed throughout the twenty-eight days of storage. Meanwhile, quality changes were observed in the samples after thermal processing where sterilization caused significant changes in the peroxide value, texture profile, and overall sensory quality of calamay. On the other hand, the pasteurization process was more effective in retaining the original quality of calamay where only the overall sensory quality through sensory evaluation has perceived significant changes were only observed in the calamay samples after its thermal processing while no changes were observed throughout its storage. It is recommended to conduct further research to develop calamay formulation that is appropriate for thermal processing which would maximize the retention of the original calamay quality.